Ethnobotanical study of Acanthaceae family in Kantarawichai District, Maha Sarakham Province, Thailand - PIYAPORN SAENSOUK; AREERAT RAGSASILP; NICHA THAWARA; THAWATPHONG BOONMA; SOMBAT APPAMARAKA; ANOUSONE SENGTHONG; HANVEDES DAOVISAN; AHMAD DWI SETYAWAN; SURAPON SAENSOUK (Society for Indonesian Biodiversity, 2024)
Abstract. Saensouk P, Ragsasilp A, Thawara N, Boonma T, Appamaraka S, Sengthong A, Daovisan H, Setyawan AD, Saensouk S. 2024. Ethnobotanical study of Acanthaceae family in Kantarawichai District, Maha Sarakham Province, Thailand. Biodiversitas 25: 2570-2582. Traditional botanical knowledge plays a crucial role in the cultural and medicinal practices of indigenous communities, yet it is increasingly at risk of being lost. This study aims to document and analyze the use of Acanthaceae species by villagers in two villages in Kantarawichai District, Maha Sarakham Province, Thailand to preserve this knowledge and support sustainable resource management. Data on traditional botanical knowledge of Acanthaceae from villagers were collected using semi-structured interviews. The data were then analyzed by using Use Value (UV), Cultural Importance Index (CI), and Informant Agreement Ratio (IAR). The study found nine species with two variations belonging to seven genera in the Acanthaceae family that are used by villagers, namely Andrographis paniculata (Burm.f.) Wall. ex Nees, Asystasia gangetica (L.) T. Anderson, Barleria prionitis L., Justicia adhatoda L., J. gendarussa Burm.f. (Kra Duk Kai Khaw), J. gendarussa Burm.f. (Kra Duk Kai Dum), Rhinacanthus nasutus (L.) Kurz, Ruellia tuberosa L., and Ru. simplex C.Wright. They can be classified into four groups based on their uses: foods, medicine, religious plant and other uses. Species with the highest Use Value (UV) and Informant Consensus Factor (ICF) was Rh. nasutus (L.) Kurz which is used in many respects. The highest IAR value of 0.79 was Thunbergia laurifolia Lindl. followed by An. paniculata (Burm.f.) Wall. ex Nees (0.70) and Rh. nasutus (L.) Kurz (0.33), indicating the agreement among informants mentioned the plant species for particular disease. This study emphasizes the importance of transmission of traditional knowledge to prevent it from disappearing in the future and to inform natural resource management of local people for conservation and sustainable development.